La Habana del Este Atlas del patrimonio territorial - Spellucci, Simone (Territori, 2022)
The Atlas of Territorial Heritage in the Municipality of East Havana is a useful tool in order to reach a complete knowledge of an extended Cuban municipality belonging to Havana, Cuba. At the same time the atlas is useful to generate analytical bases for future urban planning interventions and transformations, which can be focused on the idea of territorial heritage as an essential resource for a self-sustaining development. The main objective is to explain the tangible and intangible components of the heritage and try to stimulate and strengthen the community's awareness on the richness of territory and its potential. Thus communities can express themselves in the adaptation to environmental, climatic, demographic and economic changes. The Atlas was developed by an Italian/Cuban team of experts in different phases and has been updated recently. It contains the results of a deep and accurate analysis and cataloging, made up of a large number of data concerning the various areas of research. The data were organized in typologies and punctually located in maps. The multifaceted and dense richness of Cuban culture finds in this volume a confirmation, and makes possible to put into practice cognitive tools for safeguarding and valorization, a strong point for new challenges of contemporaneity.